Γ-group congruences on regular Γ-semigroups - A. Seth (International Journal of Mathematics and Mathematical Sciences)
In this paper a Γ-group congruence on a regular Γ-semigroup is defined, some equivalent expressions for any Γ-group congruence on a regular Γ-semigroup and those for the least Γ-group congruence in particular are given.